2016
DOI: 10.1177/0486613415594159
|View full text |Cite
|
Sign up to set email alerts
|

Can Public Policies Bring about the Democratization of the Outsourcing of Household Tasks?

Abstract: For twenty years or so, the outsourcing of household tasks has been considered to be increasing in many countries. In some countries (particularly in France), extensive public policies have been put in place to develop demand and create employment by explicitly seeking to democratize consumption, which still predominantly concerns more affluent households. By using both quantitative and qualitative data, this paper aims to gain a better understanding of the factors of demand for these services and to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Various studies have documented that domestic cleaning service suppliers attempt to professionalise service delivery, but they do not provide the professionalism of domestic workers (Abasabanya et al, 2016, p. 3;Devetter, 2015). For example, Cruz and Abrantes (2014, p. 431) argue that in Portugal, domestic cleaning service suppliers "often act as labour brokers rather than actual employers and represent the strategic interests of customers rather than those of domestic workers".…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have documented that domestic cleaning service suppliers attempt to professionalise service delivery, but they do not provide the professionalism of domestic workers (Abasabanya et al, 2016, p. 3;Devetter, 2015). For example, Cruz and Abrantes (2014, p. 431) argue that in Portugal, domestic cleaning service suppliers "often act as labour brokers rather than actual employers and represent the strategic interests of customers rather than those of domestic workers".…”
Section: Introductionmentioning
confidence: 99%
“…However, changing life cycles, as is the case of empty-nest households, indicate that outsourced housecleaning services are filling a particular niche in the market, by providing greater flexibility and freedom of choice to clients, that the employment of domestic workers in a full-time or part-time employment relationship is not providing. Thus, housecleaning services are providing expertise, convenience, and the flexibility to adapt to changing needs with proficiency (Devetter, 2015: 365; Devetter and Rousseau, 2009: 311). However, the long-term effects of domestic cleaning services are potentially far-reaching, given that households are becoming smaller with the rise in single-person households and childless couples.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that there are several reasons why outsourced domestic cleaning services are sought after by some people. Outsourcing cleaning and laundering duties to domestic cleaning companies free up time for clients to spend on essential activities, such as income-generating work, family responsibilities, and leisure (Devetter, 2015: 365; Du Toit and Heinecken, 2021: 1156). Outsourced domestic cleaning services can be procured on a flexible ad hoc or regular basis, depending on clients’ needs.…”
Section: Domestic Work and Outsourced Domestic Cleaning Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of the entire domestic market structure, Wang Xiruo et al (2019) discussed the optimal structure and highest efficiency of the domestic market under the condition of complete and incomplete information [3] . At the same time, foreign scholar Devetter and Franç ois-Xavier (2016) pointed out that in order to stimulate demand and create jobs, many Western countries have formulated a variety of policies for the outsourcing of household services, and through qualitative and quantitative analysis of the factors affecting the demand for domestic services, It is concluded that the consumer market for housekeeping services lacks democracy and equality [4] . Kristin K. Kucsma and Kenneth T. Betz (2018) believe that domestic services are non-market activities provided within the family, but the market value of domestic services needs to be determined in a reasonable way, and pointed out that it is necessary to increase the average wage rate to produce a corresponding alternative market hourly wages, thereby more accurately assessing family services [5] .…”
Section: Related Literature Researchmentioning
confidence: 99%